2017
DOI: 10.18632/oncotarget.22232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine infusion for intravenous patient-controlled analgesia on the quality of recovery after laparotomy surgery

Abstract: BackgroundThe Quality of Recovery-15 (QoR-15) is a patient-centered questionnaire to evaluate the recovery after surgery and anesthesia. Dexmedetomidine has sedative, analgesic, antiinflammatory and inhibitory sympathetic effects, which may contribute to early recovery. We hypothesized dexmedetomidine added to intravenous patient-controlled analgesia (PCA) could enhance the quality of recovery (QoR) in patients undergoing laparotomy surgery.MethodsIn this randomized, double-blind, controlled study, 100 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
3
14
0
Order By: Relevance
“…Furthermore, nocturnal administration of low-dose DEX in critically ill patients reduced the incidence and duration of delirium (Skrobik et al, 2018). DEX used for patient-controlled analgesia (PCA) reduced pain and adverse effects and improved patient satisfaction after surgery (Xin et al, 2017). However, few studies have evaluated the efficiency of DEX used for PCA against POD and early POCD.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nocturnal administration of low-dose DEX in critically ill patients reduced the incidence and duration of delirium (Skrobik et al, 2018). DEX used for patient-controlled analgesia (PCA) reduced pain and adverse effects and improved patient satisfaction after surgery (Xin et al, 2017). However, few studies have evaluated the efficiency of DEX used for PCA against POD and early POCD.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no significant difference between Groups C and D with regard to the supplemental requirement for tramadol. Of note, the analgesic and opioid dose-reducing/sparing effects of DEX have been well documented in previous studies in adult and pediatric patients (7,8,27). Together with these results, the present study demonstrated that pre-operative administration of 0.5 µg/kg DEX and the administration of DEX in combination with sufentanil PCIA provided effective analgesia following tangential excision skin grafting.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, similar results were obtained in a previous study for thoracic surgery where an infusion dose of 0.04 µg/kg/h DEX in combination with 0.02 µg/kg/h sufentanil reduced post-operative pain during the initial 72 h post-surgery (26). In the present study, DEX was administered at an infusion dose of ~0.03 µg/kg/h DEX, which is an approach that has been used for patient-controlled analgesia in Asian patients (7). The present results indicated that the combined use of DEX with sufentanil had an improved capacity to relieve post-operative acute pain at rest and during movement compared with sufentanil alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have demonstrated that dexmedetomidine significantly reduced lipopolysaccharide (LPS)-induced secretion of pro-inflammatory cytokines, such as tumor necrosis factor (TNF)-α, interleukin (IL)-6 and IL-8 (13). In clinical practice, studies have illustrated similar anti-inflammatory effects although inconsistencies between studies exist (13)(14)(15)(16)(17)(18). Dexmedetomidine also reduces patients' need for anesthetic treatment (19), and can reduce the blood pressure and heart rate of patients in a dose-dependent manner (20).…”
Section: Introductionmentioning
confidence: 99%